(untitled) (Global Journal of Human-Social Science, 2014)
Mining has a significant impact on the economic, social and environmental fabric of adjoining areas. Although mining activities bring about economic development in the area, at the same time the land degradation causes ecological Mining adversely affects the ecoassessment studies to learn the potential adverse impact of mining on flora and fauna. To overcome from the problems one should have knowledge about the various activities of environmental concern. As we have seen earlier time that every mine managers keep check list giving information on environmental controls, as envisaged in various mining conditions of the Government of India and Environment management plan. Frequent review of this information may enable identification of the site at the mine. Poor environmental performance may accele regulatory conditions. Therefore, the task is to make continuous efforts towards environmental improvement by each mine authority. The present paper discusses on various risks involved around coal mines activities in India. It also deals with the rights of the people to live in clean environment.